Views of Struggling Students from Historically Excluded Groups on Academic Success and Instructor Support - Amy Collins-Warfield; Jera Niewoehner-Green; Scott Scheer; Kristen Mills (Journal of Postsecondary Student Success, 2023)
This qualitative case study explored the perceptions of struggling students who identified as first-generation, low-income, and/or Students of Color (i.e., Historically Excluded Groups), and their beliefs about success, struggle, and characteristics of supportive instructors. Thematic analysis revealed student participants understood academic success and struggle in terms of Identifying Performance Measures, Developing a Growth Mindset, and Integrating Knowledge. Students identified supportive instructors by using one or more of the following themes, which were described using in vivo codes: Creates More Motivation for Me, Puts the Joy into Learning, Doesn’t Make You Feel Dumb, Not Here to Hurt Your Grades, Makes Material Understandable, Treats Us as More Than Just Students, and If I Ever Needed Anything. Implications for practice include expanding the definition of academic success and engaging specific instructor dispositions and behaviors to better support these students.